Reading to Be Free: Rewriting the Story that Oppression Tells Every Day (KULT_online, 2016)
Through a “socioformal” approach applying social and cultural psychology to literary criticism, Paula M. L. Moya argues for the discipline’s potential to contribute to the study of the “world-making social fictions” of race, ethnicity, gender, and sexuality (p. 1). Deeply written into the consciousness and cultural imaginary, the self is the story we are told, and tell, every day. Regular, brutal self-examinations, or close readings of the self, are instrumental in resisting oppressive external readings and achieving personal as well as social transformation. And literature possesses the tools to survey and deconstruct the fictional mechanics of oppression at the levels of self-concept and the concept of the other. Since multicultural literature provides readers access to subordinated individuals’ schemas, literature “is one of the key sites in which the social order can be imaginatively examined and reshaped” (p. 40).